Observational studies of the effects of wind mixing and biological process on the vertical distribution of dissolved oxygen off the Changjiang Estuary - Miao, Yanyi; Wang, Bin; Li, Dewang; Sun, Xiangyu; Xu, Zhongsheng; Sun, Qianwen; Jiang, Zhibing; Ma, Xiao; Jin, Haiyan; Chen, Jianfang (Frontiers in Marine Science, 2023)
Wind mixing is important in regulating dissolved oxygen (DO) variability; however, the transect response of DO dynamics to wind disturbance has seldom been documented with field data. In the summer of 2017, repeat transect observations off the Changjiang Estuary were conducted throughout a fresh wind (the maximum wind speed was 9.8 m s–1) event to reveal the role of physical mixing and biological activity in DO variations. After the wind event, hypoxia was alleviated presenting as the hypoxia thickness decreased from 30 m to 20 m. However, poorly ventilated near-bottom hypoxia was aggravated with a further decrease in DO. Generally, the saturation of dissolved oxygen (DOs) in depth-integrated water column increased by 9%–49% through physical diffusion with a weakened stratification and enhanced phytoplankton bloom. However, in this case, the wind-induced physical water mass mixing by transporting DO downward had a limited contribution to the water-column DO budget, while upwards nutrients induced by mixing fueled the larger vertical area of algae bloom and subsequent substantial oxygen consumption. As the wind speed increased, the air-sea exchange would be important in supplying DO, especially in nearshore areas, which could effectively offset the DO deficiency. In summary, frequently occurring fresh wind-mixing events off the Changjiang Estuary would alleviate hypoxia in the water column but probably exacerbate hypoxia at the bottom, as determined by competing ventilation and respiration roles. Such complex interactions likely occur and perform differently as wind stress varies. Thus, high-spatial and long-term process observations are required to better understand the net effects of bottom hypoxia evolution.